Targeted delivery of rifaximin using P6.2-decorated bifunctional PLGA nanoparticles for combating Staphylococcus aureus infections - Arayici, Pelin Pelit; Coksu, Irem; Ozbek, Tulin; Acar, Serap (ELSEVIER, 2024)
The emergence of antibiotic resistance makes the treatment of bacterial infections difficult and necessitates the development of alternative strategies. Targeted drug delivery systems are attracting great interest in overcoming the limitations of traditional antibiotics. Here, we aimed for targeted delivery of rifaximin (RFX) by decorating RFX-loaded poly(lactic- co -glycolic acid) (PLGA) nanoparticles (NPs) with synthetic P6.2 peptide, which was used as a targeting agent for the first time. Our results showed that encapsulation of RFX into NPs increased its antibacterial activity by improving its solubility and providing controlled release, while P6.2 modification allowed targeting of NPs to S. aureus bacterial cells. A promising therapeutic approach for bacterial infections, these P6.2 -conjugated RFX-loaded PLGA NPs (TR-NP) demonstrated potent antibacterial activity against both strains of S. aureus . The antibacterial activity of RFX-loaded PLGA NPs (R -NP) showed significant results with an increase of 8 and 16 -fold compared to free RFX against S. aureus and MRSA, respectively. Moreover, the activity of targeted nanoparticles was found to be increased 32 or 16 -fold with an MBC value of 0.0078 mu g/mL. All nanoparticles were found to be biocompatible at doses where they showed antimicrobial activity. Finally, it revealed that P6.2 -conjugated targeted nanoparticles extremely accumulated in S. aureus rather than E. coli .
Keywords: Antimicrobial peptide; Drug delivery; Nanoparticle; Poly(lactic; co -glycolic acid); Rifaximin; S. aureus; CONJUGATED NANOPARTICLES; ANTICANCER ACTIVITY; IN-VITRO; ANTIBACTERIAL; RELEASE; SOLVENT; DISEASE; SYSTEM; Materials Science